Power for All by 2012: Bottlenecks and Strategies for Mission - Jain, Nisha (Journal of Commerce and Trade, 2012)
The nuclear, hydro, and thermal energy are the prominent sources of electricity generation in India. The Central Ministry of Power is the main authority responsible for the overall development of electrical energy. The ministry is in charge of planning, formulating policies, monitoring and implementing power projects, processing of projects for investment decision, and enacting legislation with regards to power generation, distribution, and transmission. In order to attract foreign investments into the power industry of India, the government has announced several policies and has taken initiatives from time to time. The most important amongst all the policies announced by the government is the enactment of the Electricity Act. The act was enacted in 2003. The act mainly aims to solidify the existing laws relating to the generation, distribution, transmission, and trading of electricity, promote healthy competition among companies in the power sector; and ensure that there is a supply of electricity to every nook and corner of the country. The Electricity Act also aims to rationalize electricity charges, promote efficient and environmentally favorable policies. Moreover, the Central Ministry of Power has set an ambitious plan of “power for all by 2012”. While the power sector in India has witnessed a few success stories in the last 4-5 years, the road that lies ahead of us is dotted with innumerable challenges that result from the gaps that exist between what’s planned versus what the power sector has been able to deliver.